347 Outcomes of patients undergoing extremely high complexity surgery (EHCS) for advanced ovarian cancer, a single centre review of practice. (13th November 2020) - Watson, L; Hall, T; Asher, V; Bali, A; Abdul, S; Phillips, A
Abstract : Introduction: The surgical complexity score (SCS) divides surgical extent by score into 3 categories; Low (0–3), Intermediate (4–7) and High (8+). This study addressed patients whose surgery for advanced ovarian/peritoneal/tubal epithelial cancer (AOC) scored ≥12. The outcomes following such extensive surgery are poorly described in the literature. Methods: A retrospective review of surgical and oncological outcomes of all patients diagnosed between 17/2/16–14/5/19 with AOC treated with a SCS of ≥12. Results: 11 patients received EHCS over 38 months, mean age 58. Median SCS was 13 (Range 12–16). 10 patients had serous cancer (grade 1=1, grade 3=9) and 1 had carcinosarcoma. 7 patients (63.6%) underwent primary debulking surgery and 4 (36.4%) interval debulking. All patients required diaphragmatic surgery, six (54.5%) required splenectomy and five (45.5%) paracardiac node resection. Mean blood loss was 1838 ml, mean operating time was 489 minutes (range 323–613). Complete cytoreduction was achieved in 10/11 patients (91%), 1 patient had <1 cm residual disease on small bowel serosa. 91% (10/11) patients received adjuvant chemotherapy with a median time to initiation of 55.5 days. Major grade 3 morbidity occurred in 4/11 (36%) of patients (Return to theatre (n=2) and thoracocentesis (n=2)). There were no grade 4 or grade 5 complications and no deaths within 30 days. At time of analysis three patients had died. Median OS had not been met with a 3 year survival of 71%. Conclusion: Surgery involving EHCS is safe and feasible. Larger data collection is needed to better inform both patients and clinicians on expected outcomes.